P044 Regional differences in use of getcheckedonline and client characteristics across british columbia, canada. (14th July 2019) - Ablona, Aidan; Korol, Ellen; Gauthier, Barbara; Campeau, Laurence; Bannar-Martin, Sophie; Karlsson, Maja; Hiscoe, Lorena; Hoyano, Dee; Haag, Devon; Grennan, Troy; Gilbert, Mark
Abstract : Background: GetCheckedOnline (GCO) launched in Vancouver, British Columbia (BC), Canada, in September 2014, offering online access to sexually-transmitted infection (STI) testing. In February 2016, the program expanded to smaller urban, suburban, and rural communities in south central BC (Interior Health Authority) and Vancouver Island (Island Health Authority). Given regional differences in STI clinic service availability, we used GCO program data to compare socio-demographic and behavioural measures by region among clients completing testing through GCO. Methods: GCO test episode and client-level data were included from the first 23 months of regional expansion (February 2016 to December 2018). Variables were analyzed descriptively. Bivariate analyses comparing Vancouver with each of the expansion regions (Island and Interior) were conducted using chi-squared tests; significant results (p<0.05) are listed below. Results: During the study period, 6, 329 unique clients completed testing, with 3, 435 (54%) from Vancouver, 1, 834 (29%) from Island, and 1, 060 (17%) from Interior. In total, 10, 953 test episodes were completed. STI positivity was higher in Interior compared to Vancouver (6.1% vs 4.8%). Vancouver testers were older and a higher proportion identified as men who have sex with men (35%) compared to Interior (14%) and Island (26%). Greater proportions of testers from the expansion regions were symptomatic and reported STI risk factors (contact with STI-positive partner, condomless sex with >1 partner) at time of testing. Higher proportions of testing events in expansion regions were reported as first-time STI tests (never tested before: 23% Interior and 15% Island vs 9% Vancouver). Conclusion: This study highlights important regional differences in socio-demographic and sexual risk behaviours among GCO clients. Further research describing predictors of STI positivity, repeat testing patterns, and differences in barriers to testing across regions will help contextualize the impact of an online STI testing service across urban, suburban, and rural environments. Disclosure: No significant relationships.